Evaluation of the physical, electrical, and magnetic properties of iron sand and its potential applications for advanced technology - Sony Hidayat; Agus Yulianto (Journal of Physics: Theories and Applications, 2025)
This study examines the physical, electrical, and magnetic properties of iron sand from Bayuran Beach to evaluate its potential as a functional material in advanced technology applications. Iron sand samples with particle sizes between 100 and 300 mesh were analyzed using the two-point method, LCR meter, and X-ray Diffraction (XRD). The XRD results indicate that the samples are dominated by the magnetite phase (Fe₃O₄). The 150 mesh sample showed the highest resistivity of 3.38 × 10⁹ Ω·m and a maximum capacitance of 0.16 nF. The magnetic susceptibility value reached 3.34 × 10⁻⁴ m³/kg, with a magnetic mineral content of 79.80% and a density of 2.52 g/cm³. These findings indicate that Bayuran iron sand has strong potential as a soft magnetic material for inductor cores and magnetic field sensors, microwave absorbers for electromagnetic applications, and dielectric substrates in electronic systems. The capacitance variation between dry and wet conditions also indicates its potential as a humidity sensor. Furthermore, the presence of the Fe₃O₄ phase opens up opportunities for further development as an electrode material in supercapacitors or other energy storage devices through morphological engineering. Overall, this local iron sand is a promising candidate for development into a natural resource-based functional material.